The effect of operating fracturing parameters on fracture conductivity and proppant mass requirement for tight Oligocene reservoir - Nguyen Huu Truong; Nguyen Quoc Dung; Pham Dinh Phi; Nguyen Nguyen Viet Khoi (Petrovietnam Journal, 2018)
The authors used the experimental central composite design (CCD) and optimum response surface methodology (RSM) to investigate the effect of four operating fracturing parameters on fracture conductivity during hydraulic injection in the Oligocene reservoir. By using the RSM method, the maximised fracture conductivity has been determined according to four optimum factors including leak-off coefficient, proppant concentration, injection time, and injection rate. The correlation between the responses of fracture conductivity and four parameters has been presented in the research with the confident coefficient factor of R square of 0.995 and R square adjust of 0.990. The results showed that the maximum fracture conductivity was 1,300md.ft with optimal leak-off coefficient of 0.0031ft/min0.5, injection rate of 40bpm, injection time of 96 minutes, and proppant concentration of 10ppg.